A group decision making sustainable supplier selection approach using extended TOPSIS under interval-valued Pythagorean fuzzy environment. (1st May 2019) - Yu, Chunxia; Shao, Yifan; Wang, Kai; Zhang, Luping
Highlights: A group decision making sustainable supplier selection approach using extended TOPSIS based on IVPFSs is proposed. The IVPFSs are used to capture decision maker's uncertainty information. An extended TOPSIS method integrating distance and similarity based on IVPFSs is proposed to evaluate suppliers. Abstract: Due to the increasing awareness of environmental and social issues, sustainable supplier selection becomes an important problem. The aim of this paper is to develop a novel group decision making sustainable supplier selection approach using extended Techniques for Order Preferences by Similarity to Ideal Solution (TOPSIS) under interval-valued Pythagorean fuzzy environment. Sustainable supplier selection often involves uncertain information due to the subjective nature of human judgments, and the interval-valued Pythagorean fuzzy set (IVPFS) has great ability to address strong fuzziness, ambiguity and inexactness during the decision-making process. The first contribution of this research is to use the IVPFS to capture the uncertain information of decision makers. Moreover, sustainable supplier selection often involves multiple decision makers from different groups. The second contribution of this research is to develop a group decision making approach for sustainable supplier selection. TOPSIS is the most commonly used technique in sustainable supplier selection. The third contribution of this research is to propose an extended TOPSIS method by integrating distance and similarity between alternatives concurrently to evaluate performances of suppliers. In this research, the group decision making approach and extended TOPSIS method is also extended to IVPFSs. Finally, experiments are conducted to verify the feasibility and efficiency of the proposed sustainable supplier selection approach. Experiments results show that the proposed approach is effective and efficient to help decision makers to select optimal sustainable suppliers. Therefore, the proposed approach can be applied by managers to evaluate and determine appropriate suppliers in sustainable supplier selection process.